2010
DOI: 10.1111/j.1365-2966.2010.17167.x
|View full text |Cite
|
Sign up to set email alerts
|

The R136 star cluster hosts several stars whose individual masses greatly exceed the accepted 150 M⊙ stellar mass limit

Abstract: Spectroscopic analyses of hydrogen-rich WN 5-6 stars within the young star clusters NGC 3603 and R136 are presented, using archival Hubble Space Telescope and Very Large Telescope spectroscopy, and high spatial resolution near-IR photometry, including Multi-Conjugate Adaptive Optics Demonstrator (MAD) imaging of R136. We derive high stellar temperatures for the WN stars in NGC 3603 (T * ∼ 42 ± 2 kK) and R136 (T * ∼ 53 ± 3 kK) plus clumping-corrected mass-loss rates of 2-5 × 10 −5 M yr −1 which closely agree wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

59
710
7
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 552 publications
(777 citation statements)
references
References 110 publications
59
710
7
1
Order By: Relevance
“…[107] found three stars in the Large Magellanic Cloud (metallicity ∼ 0.5 times solar) with current masses in excess of 150 M ⊙ . If this means that stars can form up to hundreds of solar masses, then [108] found that > ∼ 100 M ⊙ − 100 M ⊙ black hole mergers might originate in massive stellar binaries.…”
Section: Implications For Black Hole Binary Formationmentioning
confidence: 99%
“…[107] found three stars in the Large Magellanic Cloud (metallicity ∼ 0.5 times solar) with current masses in excess of 150 M ⊙ . If this means that stars can form up to hundreds of solar masses, then [108] found that > ∼ 100 M ⊙ − 100 M ⊙ black hole mergers might originate in massive stellar binaries.…”
Section: Implications For Black Hole Binary Formationmentioning
confidence: 99%
“…Crowther et al 2010), we estimate in total log(L He ii ) ≈ 38.6. This estimate is based on a synthetic model for the LMC WN5h star VFTS 682 from Bestenlehner et al (2011) with log(L/L ) = 6.5 and log(L He ii ) = 37.5, which was scaled to the total luminosity of the seven objects (log(L/L ) = 7.58 ± 0.03, as obtained from Crowther et al 2010;Hainich et al 2014;Bestenlehner et al 2014). We note that this value is uncertain as for some of the stars different luminosities have been obtained in different works, and one of the stars, Mk 34, is a known binary.…”
Section: Vms In Young Massive Clustersmentioning
confidence: 99%
“…Hamann et al 2006;Crowther et al 2010;Hainich et al 2014;Bestenlehner et al 2014). The HRD positions of these objects suggest that they are very massive stars (VMS) with initial masses in excess of ∼100 M , and reaching up to 300 M (cf.…”
Section: Wr Populations In the Galaxy And Lmcmentioning
confidence: 99%
“…There are potentially two ways this can be done: the inclusion of rotating massive stars (Levesque et al 2012;Leitherer et al 2014); and/or the inclusion of very massive stars (Crowther et al 2010;Doran et al 2013). We consider each in turn.…”
Section: Ionizing Fluxesmentioning
confidence: 99%